Preliminary genetic characterization of slipper-shaped oyster, Crassostrea iredalei (Faustino 1932) from Batutay Bay Samar using microsatellite markers - Germinal, Christine Faith G.
Oyster production is essential especially in the Philippine archipelago due to its economic importance in both the trading industry and local use. Slipper-shape oyster, C. iredalei, receives particular attention due its large size however, the culture stock in local aquaculture comes mostly from wild populations thus there is no control over the quality of the oyster. The lack of the genetic profile makes it difficult to do a successful selective breeding. Microsatellite markers or simple sequence repeats (SSRs) mostly occur in the non-coding region of the DNA and proved to be useful in investigations of genetic variability and inbreeding, parentage assignments and the construction of high-resolution genetic linkage maps. The objective study of this study was to establish a genetic profile of the population of C. iredalei by determining the microsatellite alleles present with the use different optimized primers. Results showed that CI.A11 was optimized at 51.9°C by amplifying two alleles with 526.7 and 190.8 bp sizes respectively and CI.B07 was optimized at 56.1°C with 148 bp and 130.9 bp sizes. Furthermore, the optimized primers were used on different DNA samples. In CI.A11, three individuals (Sam4c, Sam25a, Sam23a) showed multiple bands indicating polymorphism in the population. In CI.B07, two samples (Sam25a and Sam28a) showed 4-5 alleles with base pair sizes ranging from 123-157 bp and 500-1000 bp indicating high polymorphism whereas the other two samples (Sam4c and Sam23a), only showed 2-3 alleles with base pair sizes ranging from 123-200 bp and 500-600 bp indicating low level of polymorphism. The optimized primers used in the study can be further utilized in other different DNA samples to determine the alleles and can help in the establishment of the genetic of C. iredalei in Batutay Bay, Samar.